MONETARY POLICY OF GEORGIA IN XI-XII CENTURIES AND ITS INFLUENCE ON THE INTERNATIONAL FINANCIAL AND ECONOMIC RELATIONS - ABUSELIDZE, George (Theoretical and Practical Research in Economic Fields, 2018)
This works we have researched the matters of formation of monetary policy of feudal age and their effect on development of foreign trade, methods of money formation important for the present world, which correct choice may provide increase of production volume and economic activity. Currency policy, geopolitical and geostrategic localization proved the country to turn into one of the economically strong economic states with high standard of life, developed system of socioeconomic relations approached to the international standards and democratic institutions.